PROBLEMS IN LEARNING TO READ AND WRITE AL-QURAN AT TPQ AL-IKHLAS NGORO MOJOKERTO - Salas Asani Nishfi Romadhon; Imam Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the internal and external factors that cause difficulties inlearning to read and write the Qur'an (BTQ), as well as knowing the efforts made toovercome the problems of learning to read and write the Qur'an (BTQ) at TPQ Al-IkhlasNgoro Mojokerto. Using a qualitative phenomenological approach, this study exploresthe experiences of students, teachers, and parents of the obstacles that occur in thelearning process. Data collection used in the form of observation, documentation andinterviews with teachers, students and parents. The results showed that internal factors,namely (1) the uneven ability of students, (2) low learning motivation, (3) weakdiscipline, (4) limited teacher competence in methodology greatly affects theeffectiveness of learning, (5) lack of media and learning aids. While external factorsinclude (1) lack of parental support, (2) unsupportive social environment, (3) limitedfacilities and infrastructure, (4) no structured curriculum. To overcome these variousobstacles, TPQ Al-Ikhlas has made various efforts such as involving parents in thelearning process, (1) improving infrastructure, (2) compiling a more systematiccurriculum, (3) developing more interactive learning methods. This research is expectedto be a reference for other Islamic educational institutions in improving the quality ofBTQ learning.